2012
DOI: 10.1038/mt.2012.155
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TCTP as a New Therapeutic Strategy in Castration-resistant Prostate Cancer

Abstract: Heat shock protein 27 (Hsp27) is highly overexpressed in castration-resistant prostate cancer (CRPC) and an antisense inhibitor (OGX-427) is currently in phase II clinical trials. In order to understand mechanisms of action of Hsp27 and find new therapeutic targets specific of CRPC, we screened for Hsp27 client proteins. Here, we report that translationally controlled tumor protein (TCTP) is a new Hsp27 client protein involved in Hsp27 cytoprotection. We found that TCTP expression is absent or weak in normal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 47 publications
(61 reference statements)
5
93
0
Order By: Relevance
“…Another example of TCTP being involved in advanced state malignant disease came from a study on prostate cancer (PC). Baylot et al demonstrated that TCTP is particularly expressed in the castration-resistant form of PC and in metastases of the bone, liver and lymph nodes resulting from this (Baylot et al 2012). Their results also show that knockdown of TCTP inhibits growth of prostate cancer cells, progression of castration-resistant tumours in mice and reduces their chemoresistance to docetaxel.…”
Section: Mechanistic Involvement In Cancer Progressionmentioning
confidence: 95%
See 3 more Smart Citations
“…Another example of TCTP being involved in advanced state malignant disease came from a study on prostate cancer (PC). Baylot et al demonstrated that TCTP is particularly expressed in the castration-resistant form of PC and in metastases of the bone, liver and lymph nodes resulting from this (Baylot et al 2012). Their results also show that knockdown of TCTP inhibits growth of prostate cancer cells, progression of castration-resistant tumours in mice and reduces their chemoresistance to docetaxel.…”
Section: Mechanistic Involvement In Cancer Progressionmentioning
confidence: 95%
“…In their study, they used a mouse model to show that treatment with the TCTP-ASO inhibits tumour growth in castrationresistant prostate cancer, enhances docetaxel chemotherapy and delays cancer progression in vivo. This effect is associated with an increase in P53 levels (Acunzo et al 2014;Baylot et al 2012). In addition, recently a peptide aptamer (WGQWPYHC) targeting TCTP was tested and found to display specific cytotoxicity towards TCTP expressing tumour cells, without affecting normal cells (Kadioglu and Efferth 2016).…”
Section: Tctp As An Anticancer Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researches show that TCTP level in tumor is higher than that in the corresponding normal tissues, indicating its critical role in tumorigenesis (Amson et al, 2011;Amson et al, 2013). Among 20 screened proteins in lung cancer, TCTP is one of the most overexpressed proteins in human lung cancer cells compared with the normal cells, suggesting that TCTP can be a good biomarker for lung cancer ( Lo et al, 2012;Baylot et al, 2012;Acunzo et al, 2014).…”
Section: Targeted Efficacy Of Dihydroartemisinin For Translationally mentioning
confidence: 99%